TIPOLOGI INTERAKSI SOSIAL DALAM MENINGKATKAN KARAKTER DISIPLIN SISWA - Muhammad Mushfi El Iq Bali; Abwabun Naim (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
The purpose of this study is to improve the discipline of MA Darul Lughah Wal Karomah Sidomukti Kraksaan students with typologies of social interaction. The typology of social interaction includes the application of a point system, the application of the teacher's example in fostering student attitudes and discipline, and the application of a reward and punishment system. This type of research uses a qualitative research approach with research procedures that produce descriptive data in the form of written or oral words from people and observable behaviour. This type of research is descriptive type intended to describe various conditions and things as they are. The data used are primary data types and secondary data. The data analysis techniques in this study used the Miles and Huberman model techniques. Based on the results of the study, the application of the point system that has been running is quite effective in improving student discipline. Furthermore, a conducive learning atmosphere is very helpful for teachers in giving examples to students. The teacher is easy to give good advice, examples of attitudes, and behaviour so that students can capture the moral messages contained in each teacher's speech, attitude, and behaviour.